Atomistic modeling of apatite-collagen composites from molecular dynamics simulations extended to hyperspace - Duchstein, Patrick; Zahn, Dirk (Journal of Molecular Modeling, 2011)
The preparation of atomistic models of apatitecollagen composite mimicking enamel at length scales in the range of 1–10 nanometers is outlined. This biocomposite is characterized by a peculiar interplay of the collagen triplehelix and the apatite crystal structure. Structural coherence is however only obtained after drastic rearrangements, namely the depletion of protein-protein hydrogen bonds and the incorporation of calcium triangles which are stabilized by salt-bridges with the collagen molecule. Starting from an isolated collagen triple helix and a single-crystalline apatite structure, a composite model is obtained by gradually merging the two components via an additional (hyperspace) coordinate. This approach allows smooth structural relaxation of both components whilst avoiding singularities in potential energy due to atomic overlap.
EAM Import::2019-03-13